Characteristics of unipolar depression in psychiatric inpatients. (13th April 2021) - Kacem, M.; Khouadja, S.; Brahim, S.; Boukhchina, R.; Zarrouk, L.
Abstract : Introduction: Unipolar depression is daily encountered in psychiatry. Objectives: To describe the socio-demographic and clinical characteristics of patients with unipolar depression. Methods: This is a cross-sectional, descriptive study carried out at the psychiatric department of the University Hospital of Mahdia. We have included patients with unipolar depression. The data were collected from patients' medical files using a pre-established 37-item questionnaire. Results: We have collected 53 patients. The mean age was 44 years. The majority of patients were female (56.6%) and unemployed (70%). 47.2% of patients were married. 72% of patients had a low socio-economic level. They were smokers in 45.3% of cases. Alcohol consumption was found in 24.5% of cases. A family history of mood disorder and suicide or attempted suicide were present in 7% and 13.2% of the cases respectively. 7% of the patients had a history of a postpartum thymic episode. The mean number of depressive episodes was 2.5. Personal history of suicide attempts was found in 40% of cases. The mean age of the first thymic episode was 35 years. At the psychiatric examination, psychomotor retardation was present in 64% of cases, anxiety distress in 58.5% of cases, psychotic, melancholic and atypical characteristics in 30%, 13.2% and 5.7% of cases respectively. 81% of patients were treated with anxiolytic drugs in combination with an antidepressant. Antipsychotic treatment was combined in 45% of cases and electro-convulsive therapy in 9.4% of cases. Conclusions: Our patients presented predictive criteria of bipolarity. Therefore, vigilance is necessary in their medical management.